2013
DOI: 10.1002/cctc.201200871
|View full text |Cite
|
Sign up to set email alerts
|

Redesign of a Phenylalanine Aminomutase into a Phenylalanine Ammonia Lyase

Abstract: An aminomutase, naturally catalyzing the interconversion of (S)‐α‐phenylalanine and (R)‐β‐phenylalanine, was converted into an ammonia lyase catalyzing the nonoxidative deamination of phenylalanine to cinnamic acid by a rational single‐point mutation. It could be shown by crystal structures and kinetic data that the flexibility of the lid that covers the active site decides whether the enzyme acts as a lyase or a mutase. An Arg92Ser mutation destabilized the closed conformation of the lid structure and convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 62 publications
1
46
1
Order By: Relevance
“…Although conversion remained more or less constant after this, the levels of each amino acid fluctuated significantly, with initial production of mostly the α-regioisomer followed by gradual accumulation of the β-product. For three of the substrates (1d, i and l) the level of the β-amino acid was found to overtake that of the classical PAL product, along with the lower final β:α ratio (48:52) for 1r and even the control substrate 1a showing significant side-product after 48 h. This production of one regioisomer first followed by the other is very different to time course experimental results with TwPAM, where the β:α ratio has been shown to remain more or less constant, even with increasing conversion over time [8]. This is most likely due to the difference in regioselectivity between PAL and PAM enzymes, whereby different kinetic constraints are imposed on the β-and α-addition reactions in combination with an apparent preference for the β-regioisomer under the reaction conditions used in this work.…”
Section: Resultscontrasting
confidence: 56%
“…Although conversion remained more or less constant after this, the levels of each amino acid fluctuated significantly, with initial production of mostly the α-regioisomer followed by gradual accumulation of the β-product. For three of the substrates (1d, i and l) the level of the β-amino acid was found to overtake that of the classical PAL product, along with the lower final β:α ratio (48:52) for 1r and even the control substrate 1a showing significant side-product after 48 h. This production of one regioisomer first followed by the other is very different to time course experimental results with TwPAM, where the β:α ratio has been shown to remain more or less constant, even with increasing conversion over time [8]. This is most likely due to the difference in regioselectivity between PAL and PAM enzymes, whereby different kinetic constraints are imposed on the β-and α-addition reactions in combination with an apparent preference for the β-regioisomer under the reaction conditions used in this work.…”
Section: Resultscontrasting
confidence: 56%
“…In fact, the metabolism of ( R )-β-PA has only been reported for microorganism with assured aminomutases or ammonia lyases genes (Szymanski et al 2009 ; Jiang et al 2015 ; Weise et al 2015 ). The activity of aminomutases is described as quite low which might explain the rather slow degradation of ( R )-β-PA using BS115 (Bartsch et al 2013 ). Also several amino acid oxidases exist with high activity towards several amines (Alexeeva et al 2002 ; Ghislieri et al 2013 ), but as yet amino acid oxidases with activity towards β-PA have not been published.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason it might be possible that BS115, in the presence of ( S )-β-PA, expresses an ammonia-lyase or 2,3 aminomutase which could convert ( R )-β-PA to cinnamic acid. The transmutation of an ammonia-lyase into a 2,3 aminomutase is possible by a single mutation and can change the functionality of a mutase to a lyase (Bartsch et al 2013 ). The vice versa functionality change of a lyase to a mutase has not yet been reported, but attempts have been made to determine the decisive amino acid residues using mutation studies of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…367 Quasiirreversible conversion of L-phenylalanine to cinnamic acid (293) by phenylalanine ammonia lyase (PAL) provided for the driving force and allowed for facile isolation of the L-b-phenylalanine product (L-290, Scheme 58C). The large structural similarity between PAM and PAL drove the research team to engineer another PAM mutant (R92S) that showed additional PAL activity, 368 which allowed for the resolution of racemic b-phenylalanine by direct deamination of D-b-phenylalanine (48% yield, 497% ee).…”
Section: Scheme 55 Chemoenzymatic Route Towards Oseltamivir As Develomentioning
confidence: 99%